Rancang Bangun Web Monitoring Data Coverage Dan Utilitasi FAT PT. Indonesia Comnets Plus KP Bangka Belitung - Siti Alfiah, Puput; Jumnahdi, Muhammad; Puriza, M Yonggi; Anzari, Yandi (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2021)
Indonesia Comnets Plus KP Bangka Belitung is a telecommunications provider that provides fiber optic (FO)-based internet network services. During 3 years of operation from 2019 to 2022, it is estimated that the problem is the lack of information provision regarding the distribution points of PT. Indonesia Comnets Plus in the Bangka Belitung area (Rinto Hariwijaya, 2022). The provision of information regarding the distribution points of the FAT (Fiber Access Terminal) is still using a manual system where the admin needs to share the location points of the FAT (Fiber Access Terminal) via messenger. With the increasing number of FAT users every year at PT. Indonesia Comnets Plus KP Bangka Belitung requires a web- based information system that shortens the time in displaying location information for FAT points (Fiber Access Terminal) in order to facilitate FAT users in obtaining FAT location information. The purpose of this research is to design and build a web that can provide geographical information about the distribution points of FAT (Fiber Access Terminal) in the Bangka Belitung Islands Province. The results of the system analysis were obtained after implementing the web for 10 days which showed the value of the questionnaire was 56.3% a good assessment.